A New Direction for China's Defense Industry - Medeiros, Evan S.; Cliff, Roger; Crane, Keith; Mulvenon, James C. (RAND Corporation, 2023)
Since the early 1980s, a prominent and consistent conclusion drawn from research on China's defense-industrial complex has been that China's defense-production capabilities are rife with weaknesses and limitations. This study argues for an alternative approach: From the vantage point of 2005, it is time to shift the focus of current research to the gradual improvements in and the future potential of China's defense-industrial complex. The study found that China's defense sectors are designing and producing a wide range of increasingly advanced weapons that, in the short term, are relevant to a possible conflict over Taiwan but also to China's long-term military presence in Asia. Part of a larger RAND Project AIR FORCE study on Chinese military modernization, this study examines the current and future capabilities of China's defense industry. The goals of this study are to 1.